Thermoregulatory responses of Australian birds to environmental challenges - Douglas, Tegan Klair (Curtin University, 2017)
Four sedentary, insectivorous, Australian passerines (White-browed Babbler, Rufous Treecreeper, Western Yellow Robin, and Australian Magpie) meet energetic requirements under challenging environmental conditions without using mechanisms such as torpor. Instead at low ambient temperature they maintain body temperature just below normothermia by increasing metabolic rate and lowering thermal conductance, a typical endothermic response. Free-ranging birds utilise behavioural strategies like communal roosting and sheltered roost sites to aid thermoregulation, but these are not essential to maintain homeothermy.